2019
DOI: 10.1089/ast.2017.1807
|View full text |Cite
|
Sign up to set email alerts
|

A Desert Cyanobacterium under Simulated Mars-like Conditions in Low Earth Orbit: Implications for the Habitability of Mars

Abstract: In the ESA space experiment BIOMEX (BIOlogy and Mars EXperiment), dried Chroococcidiopsis cells were exposed to Mars-like conditions during the EXPOSE-R2 mission on the International Space Station. The samples were exposed to UV radiation for 469 days and to a Mars-like atmosphere for 722 days, approaching the conditions that could be faced on the surface of Mars. Once back on Earth, cell survival was tested by growth-dependent assays, while confocal laser scanning microscopy and PCR-based assay were used to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…(Huwe et al, 2019). Results obtained after space exposure are shown from a series of analyses on the biofilm kombucha (Podolich et al, 2019), the cyanobacterium Chroococcidiopsis (Billi et al, 2019), the cryptoendolithic Antarctic fungus Cryomyces antarcticus (Onofri et al, 2019), and the lichens Buellia frigida (Backhaus et al , this issue) and Circinaria gyrosa (de la Torre et al , not part of this issue). A rough summary of the different studies is given in Table 5, and more details are shown in Table 6.…”
Section: Overview Of Results Within This Special Collectionmentioning
confidence: 99%
“…(Huwe et al, 2019). Results obtained after space exposure are shown from a series of analyses on the biofilm kombucha (Podolich et al, 2019), the cyanobacterium Chroococcidiopsis (Billi et al, 2019), the cryptoendolithic Antarctic fungus Cryomyces antarcticus (Onofri et al, 2019), and the lichens Buellia frigida (Backhaus et al , this issue) and Circinaria gyrosa (de la Torre et al , not part of this issue). A rough summary of the different studies is given in Table 5, and more details are shown in Table 6.…”
Section: Overview Of Results Within This Special Collectionmentioning
confidence: 99%
“…Another approach is taken by mimicking space-or Mars-like conditions in the laboratory [118][119][120]. Silicified sediments are analyzed for early signatures of life [121].…”
Section: Habitable Zonesmentioning
confidence: 99%
“…Biomarker stability/degradation have, for instance, been evaluated in desert cyanobacteria of the genus Chroococcidiopsis exposed to different types of ionizing radiation [14] and Mars conditions simulated by using the EXPOSE facility installed outside the International Space Station [15].…”
Section: Introductionmentioning
confidence: 99%
“…During the EXPOSE-R2 space mission, in the contest of the BIOlogy and Mars Experiment (BIOMEX), dried cyanobacteria were mixed with Martian mineral analogues to mimic Martian subsurface radiation conditions reached by a reduced amount of UV radiation [21], such as it could be the case within potential subsurface or endolithic habitable niches. Dried Chroococcidiopsis cells mixed with Martian mineral analogues were exposed to a total dose of 2.19 × 10 2 kJ/m and 1.94 × 10 2 kJ/m UV radiation (200-400 nm), depending on the position inside the facility and presence of a 0.1% neutral filter [15], and 0.5 Gy of cosmic ionizing radiation [22]. Exposed cells with minerals showed a reduction in the photosynthetic pigments autofluorescence to about 20% of control while DNA could not be amplified in exposed cells not mixed with minerals [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation